Collision induced vibrations in atmospheric molecules as a path to renewable radiant energy - Joseph Lanni (Discover Energy)
Abstract In addition to atmospheric wind the radiance of the sun also creates vibrationally excited molecules whose internal energy can be returned to a usable radiant form. This requires that excited molecular energy levels reach their radiative lifetime in numbers that favor induced emission. Vibrational modes which are metastable due to their high frequency can be further populated by optical transitions from thermally replenished low frequency energy states. A calculation using the gas kinetic collision rate for atmospheric CO2 and N2 shows that inelastic collisions excite an internal vibration of CO2 at the rate of 12,940 J mol−1 s−1 at NTP, (about 538 kW m−3). This high-speed transfer of kinetic energy into the infrared active bending mode of CO2 shows the prospective viability of a multi-step system in which gas thermal energy is converted to radiant energy. An effect called ‘kinetic cooling’ observed in CO2/N2 lasers shows that lasers can be used to transfer the kinetic energy of a gas into a specific molecular mode. By inducing the transition from a thermally heated CO2 mode to one of higher energy the laser enables the transfer of energy to a resonant mode in N2, causing a measurable cooling of the gas. We consider this in relation to unexpected parallels between intense water vapor emission and maximum atmospheric transparency. Radiation from thermally excited molecules evidently adds to the measured transmission, revealing the existence of metastable vibrations. This kind of spectral correlation could lead to the discovery of modes that can be induced to radiate energy drawn from the environment.